2018
DOI: 10.1021/acs.jpcc.8b03398
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Fluorination of Conjugated Molecules Enables Stable Nanoscale Assemblies on Metal Surfaces

Abstract: In molecular self-assembly on surfaces, the structure is governed by the intricate balance of attractive and repulsive forces between molecules as well as between molecules and substrate. Frequently, repulsive interactions between molecules adsorbed on a metal surface dominate in the low coverage regime, and dense self-assembled structures can only be observed close to full monolayer coverage. Here we demonstrate that fluorination at selected positions of conjugated molecules provides for sufficiently strong y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 63 publications
5
22
0
Order By: Relevance
“…Therefore, our XRD‐based finding of upright standing molecules strongly supports the notion of randomly distributed dipole moments in the m ‐2F‐6P film, as this likewise minimizes the dipole–dipole interaction energy between neighboring molecules. We note that the marked differences in the structural properties of the ortho ‐ and meta ‐substituted 6P derivatives further agree with what has recently been reported for monolayers of these compounds on Ag(111) . There, the differences have been explained by substrate‐mediated interactions and ground‐state charge transfer, which, however, can only play a minor role on SiO x both due to the upright molecular orientation and as charge transfer is not expected with the dielectric substrate.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, our XRD‐based finding of upright standing molecules strongly supports the notion of randomly distributed dipole moments in the m ‐2F‐6P film, as this likewise minimizes the dipole–dipole interaction energy between neighboring molecules. We note that the marked differences in the structural properties of the ortho ‐ and meta ‐substituted 6P derivatives further agree with what has recently been reported for monolayers of these compounds on Ag(111) . There, the differences have been explained by substrate‐mediated interactions and ground‐state charge transfer, which, however, can only play a minor role on SiO x both due to the upright molecular orientation and as charge transfer is not expected with the dielectric substrate.…”
supporting
confidence: 90%
“…However, the impact of partial substitution on the growth behavior has so far only been investigated in the monolayer regime on metals for fluorination at the meta ‐ ( m ‐2F‐6P) and ortho ‐positions ( o ‐2F‐6P), as well as for cyano‐substitution at the para ‐position (CN‐6P); for the chemical structures, see Figure a. In monolayers on Ag(111) it has been found that the subtle difference in fluorine position at one terminal phenyl ring has an eminent impact on the supramolecular organization . This is related to the highly different net dipole moments and their opposite orientation in m ‐2F‐6P and o ‐2F‐6P, the absolute values of which have been derived for the gas phase to amount to 2.2 D and 1.1 D, respectively .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental GIXD data for the o-F 2 -6P film [the synthesis of o-F 2 -6P is reported by Niederhausen et al (2018)] as grown on HOPG are shown in Fig. 3.…”
Section: Ortho-difluorosexiphenylmentioning
confidence: 99%
“…The transition from inclined to parallel molecular planes in these structures has been ascribed to the impact of intramolecular polar bonds by the authors. For o-F 2 -6P, no bulk crystal structures have been published yet, and structural characterization was limited to sub-monolayers on Ag(111) by low-temperature scanning tunnelling microscopy (Niederhausen et al, 2018). There, in contrast to non-fluorinated 6P molecules which individually adsorb in the sub-monolayer regime on the metal surface without packing, the authors find a flat lying stack arrangement of the o-F 2 -6P molecules with small lateral shifts along the row direction.…”
Section: Ortho-difluorosexiphenylmentioning
confidence: 99%